2006
DOI: 10.1176/ajp.2006.163.11.1905
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Longer-Term Outcomes in Depressed Outpatients Requiring One or Several Treatment Steps: A STAR*D Report

Abstract: When more treatment steps are required, lower acute remission rates (especially in the third and fourth treatment steps) and higher relapse rates during the follow-up phase are to be expected. Studies to identify the best multistep treatment sequences for individual patients and the development of more broadly effective treatments are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

32
1,779
8
24

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 4,254 publications
(2,008 citation statements)
references
References 50 publications
32
1,779
8
24
Order By: Relevance
“…This compares with a < 15% remission rate in the STAR*D study for subsequent antidepressant treatment in patients who had experienced two or more prospective treatment failures. 4 A recent UK RCT in patients with a similar degree of treatment resistance as in the patients in this study (mean MGHS score of 4.7), although with a lesser severity of depression (baseline mean MADRS score of 28), reported a 21% response rate and a 16% remission rate after 5 weeks in patients treated with placebo or metyrapone DISCUSSION NIHR Journals Library www.journalslibrary.nihr.ac.uk augmentation of ongoing antidepressant treatment. 162 This suggests that patients in this study received considerable clinical benefit attributable to ECT treatment.…”
mentioning
confidence: 54%
See 2 more Smart Citations
“…This compares with a < 15% remission rate in the STAR*D study for subsequent antidepressant treatment in patients who had experienced two or more prospective treatment failures. 4 A recent UK RCT in patients with a similar degree of treatment resistance as in the patients in this study (mean MGHS score of 4.7), although with a lesser severity of depression (baseline mean MADRS score of 28), reported a 21% response rate and a 16% remission rate after 5 weeks in patients treated with placebo or metyrapone DISCUSSION NIHR Journals Library www.journalslibrary.nihr.ac.uk augmentation of ongoing antidepressant treatment. 162 This suggests that patients in this study received considerable clinical benefit attributable to ECT treatment.…”
mentioning
confidence: 54%
“…The Quick Inventory of Depressive Symptomatology -Self Report (QIDS-SR) 142 is a 16-item self-rated depression scale that was used in the STAR*D study 4 and rates the nine DSM-IV depression items, each on a scale of 0-3.…”
Section: Quick Inventory Of Depressive Symptomatology -Self Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the high prevalence of resistance to treatment and failed antidepressant response, the National Institute of Mental Health developed the Sequenced Treatment Alternatives to Relieve Depression Trial, a systematic protocol for treating depression. According to the latter protocol, cumulative response and remission rates after two unsuccessful antidepressant treatments are 73% and 47% respectively 23 . Based on these data, numerous repetitive TMS (rTMS) studies have been performed on the treatment of major depressive disorder and have shown positive results, suggesting that low-frequency stimulation (1Hz) of the right dorsolateral prefrontal cortex, or high frequency over the left dorsolateral prefrontal cortex, both have antidepressant effects 24 .…”
Section: Noninvasive Transcranial Stimulation For Major Depressive DImentioning
confidence: 99%
“…This important finding highlights that the aim of treatment must be full and complete symptom resolution (symptom remission) rather than response or removal of most of the symptoms, not only to reduce the risk of relapse 4 but also to enhance recovery. This finding also aligns with other studies that have shown remission to be associated with a far better prognosis than is response without remission.…”
mentioning
confidence: 97%